Solid Waste and its Impact on the Area from Al-Shabab Lake to the Al-Arbaeen Lake on the Red Sea Coast in Jeddah - Al-Garni, Bushra Githan (Journal of natural sciences, life and applied sciences, 2020)
Costal Human activities in the region contributed to the creation of environmental issues, and to the depletion of natural resources of the coastal environments, such activities may generate an accumulation of wastes that might lead to several diseases, the spread of insects and at the same time may destruct the aesthetic of coastal areas. In line with Saudi Arabia’s 2030 Vision considering the preservation of the environment and natural capabilities, as well as to activate the environmental dimension being one of the country’s sustainable development pillars, the idea of this study prevailed, in which it addresses the solid wastes and their impact on the areas located from Al-Shabab Lake to Al-Arbeen lake on the costal side of Jeddah. The study problem can be determined by discussing the following questions, what are the types and patterns of the solid wastes within the study area? what are the most solid wastes polluted areas within the study area? what do the environmental impacts result from such type of solid wastes within the study area? The study used the descriptive, spatial and subjective analysis approaches to further understands and answer its questions. We can find out that the most important conclusions, as well as recommendations, states that the Plastic products represent the highest wastes spread within the study area (site), in controversy to the leather and cement materials, it was also observed that the cleaning service levels in the Fish Market marine areas were not acceptable, in which it recommends to further focus on the cleaning janitors and increase of their count, as well as to increase the number of waste bins across the coastal area, with a particular focus on the Central Fish Market marine area, with the enforcement of penalties on the violators whom they breach the implemented cleaning rules and drop wastes uncontrollably.